Diskursus Gender Dalam Pendidikan Islam - Rodianto (MUWAZAH : jurnal kajian gender, 2017)
Education is a media for transferring values, cultures, knowledge and capabilities in society. So, arising of gender inequalities in society, should be assumed as a result of gender bias thought in education. We found them in islamic one too. The main of its problem in Islam could be rooted from its thoughts, that assumed contain some misinterpretations of its origins and base. The reinterpretation of religious understanding which gender biased, becomes necessary and improving the content of the Islamic education curriculum by eliminating the dichotomy between men and women.